Fertilizer Source and Rate Affect Sulfur Uptake and Yield Response in Corn - T. E. Husa; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2020)
With sulfur deficiencies being found throughout Kansas, the evaluation of sulfur fertilization and plant uptake are vital to optimize corn production. The objective of this study was to evaluate the effect of application rates of sulfur on yield and uptake in corn. Nutrient concentrations in corn biomass and grain were evaluated at the Kansas River Valley Experiment Field at Rossville, KS, in 2019. Five treatments were evaluated, including a control with no sulfur and no nitrogen (N), and four fertilizer treatments with 180 lb of nitrogen and four rates of sulfur fertilizer (0, 30, 50, and 200 lb S/a). The nitrogen source was urea and balanced for all treatments at 180 lb N/a. The sulfur-containing fertilizer applications were at the time of planting corn. Whole corn plant biomass and grain samples were taken at physiological maturity and analyzed for nitrogen and sulfur concentrations. Results for the study show that sulfur application rates have a significant yield response in corn, likely contributing to increased uptake of nitrogen. Moreover, high yielding environments increased total plant sulfur uptake and removal.
Keywords: sulfur; corn; rate; yield